Lp Spaces
For any measure space (X,M,μ), one can define L2(μ) with the inner product ⟨f, g⟩:=∫Xf¯gdμ.
?
For p−1+q−1=1, with 1<p<∞, there is an isomorphism of Banach spaces κ:Lp(μ)→Lq(μ)f↦(g↦∫Xfgdμ).
This is surjective by Radon-Nikodym, and an isometry by Holder’s inequality, which is enough to be an isometric isomorphism.
General Facts
Working with inner products: ⟨tx+sy, z⟩=t⟨x, z⟩+s⟨y, z⟩⟨x, y⟩=¯⟨y, x⟩x≠0⟹⟨x, x⟩>0. We define ‖.
For x, y\in H, \begin{align*} {\left\lvert { {\left\langle {x},~{y} \right\rangle}} \right\rvert} \leq {\left\lVert {x} \right\rVert} {\left\lVert {y} \right\rVert} ,\end{align*} with equality iff x, y are linearly independent.
\begin{align*} {\left\langle {v},~{w} \right\rangle} = 0 \implies {\left\lVert {v+w} \right\rVert}^2 = {\left\lVert {v} \right\rVert}^2 + {\left\lVert {w} \right\rVert}^2 .\end{align*} More generally, if x_i \perp x_j for all i\neq j, then \begin{align*} {\left\lVert {\sum_k x_k } \right\rVert}_H^2 = \sum_k {\left\lVert {x_k} \right\rVert}_H^2 .\end{align*}
For all x, y\in H, \begin{align*} 4 {\left\langle {x},~{y} \right\rangle} = {\left\lVert {x+y} \right\rVert}^2 - {\left\lVert {x-y} \right\rVert}^2 +i\qty{{\left\lVert {x+iy} \right\rVert}^2 - {\left\lVert {x-iy} \right\rVert}^2} .\end{align*}
For all x, y\in H, \begin{align*} {\left\lVert {x+y} \right\rVert}^2 + {\left\lVert {x-y} \right\rVert}^2 = 2\qty{{\left\lVert {x} \right\rVert}^2 + {\left\lVert {y} \right\rVert}^2 } .\end{align*}
If x_k\to x and y_k\to y in H, then {\left\langle {x_k},~{y_k} \right\rangle} \to {\left\langle {x},~{y} \right\rangle}. Proof: \begin{align*} {\left\lvert {{\left\langle {x_k},~{y_k} \right\rangle} - {\left\langle {x},~{y} \right\rangle} } \right\rvert} ={\left\lvert {{\left\langle {x_n - x},~{y_n} \right\rangle} + {\left\langle {x},~{y_n-y} \right\rangle} } \right\rvert} \leq {\left\lVert {x_n - x} \right\rVert}{\left\lVert {y_n} \right\rVert} + {\left\lVert {x} \right\rVert} {\left\lVert {y_n - y} \right\rVert} .\end{align*}
Fourier Coefficients
For any orthonormal set \left\{{u_{n}}\right\} \subseteq {\mathcal{H}} a Hilbert space (not necessarily a basis), \begin{align*} \left\|x-\sum_{n=1}^{N}\left\langle x, u_{n}\right\rangle u_{n}\right\|^{2}=\|x\|^{2}-\sum_{n=1}^{N}\left|\left\langle x, u_{n}\right\rangle\right|^{2} \end{align*} and thus \begin{align*} \sum_{n=1}^{\infty}\left|\left\langle x, u_{n}\right\rangle\right|^{2} \leq\|x\|^{2} .\end{align*}
Note that this generalizes to uncountable bases, and implies that only finitely many terms {\left\langle {x},~{u_n} \right\rangle} can be nonzero.
proof (of Bessel's inequality):
-
Let S_{N} = \sum_{n=1}^N {\left\langle {x},~{u_{n}} \right\rangle} u_{n} \begin{align*} {\left\lVert {x - S_{N}} \right\rVert}^2 &= {\left\langle {x - S_{n}},~{x - S_{N}} \right\rangle} \\ &= {\left\lVert {x} \right\rVert}^2 + {\left\lVert {S_{N}} \right\rVert}^2 - 2\Re{\left\langle {x},~{S_{N}} \right\rangle} \\ &= {\left\lVert {x} \right\rVert}^2 + {\left\lVert {S_{N}} \right\rVert}^2 - 2\Re {\left\langle {x},~{\sum_{n=1}^N {\left\langle {x},~{u_{n}} \right\rangle}u_{n}} \right\rangle} \\ &= {\left\lVert {x} \right\rVert}^2 + {\left\lVert {S_{N}} \right\rVert}^2 - 2\Re \sum_{n=1}^N {\left\langle {x},~{ {\left\langle {x},~{u_{n}} \right\rangle}u_{n}} \right\rangle} \\ &= {\left\lVert {x} \right\rVert}^2 + {\left\lVert {S_{N}} \right\rVert}^2 - 2\Re \sum_{n=1}^N \overline{{\left\langle {x},~{u_{n}} \right\rangle}}{\left\langle {x},~{u_{n}} \right\rangle} \\ &= {\left\lVert {x} \right\rVert}^2 + \left\|\sum_{n=1}^N {\left\langle {x},~{u_{n}} \right\rangle} u_{n}\right\|^2 - 2 \sum_{n=1}^N {\left\lvert {{\left\langle {x},~{u_{n}} \right\rangle}} \right\rvert}^2 \\ &= {\left\lVert {x} \right\rVert}^2 + \sum_{n=1}^N {\left\lvert {{\left\langle {x},~{u_{n}} \right\rangle}} \right\rvert}^2 - 2 \sum_{n=1}^N {\left\lvert {{\left\langle {x},~{u_{n}} \right\rangle}} \right\rvert}^2 \\ &= {\left\lVert {x} \right\rVert}^2 - \sum_{n=1}^N {\left\lvert {{\left\langle {x},~{u_{n}} \right\rangle}} \right\rvert}^2 .\end{align*}
-
By continuity of the norm and inner product, we have \begin{align*} \lim_{N\to\infty} {\left\lVert {x - S_{N}} \right\rVert}^2 &= \lim_{N\to\infty} {\left\lVert {x} \right\rVert}^2 - \sum_{n=1}^N {\left\lvert {{\left\langle {x},~{u_{n}} \right\rangle}} \right\rvert}^2 \\ \implies {\left\lVert {x - \lim_{N\to\infty} S_{N}} \right\rVert}^2 &= {\left\lVert {x} \right\rVert}^2 - \lim_{N\to\infty}\sum_{n=1}^N {\left\lvert {{\left\langle {x},~{u_{n}} \right\rangle}} \right\rvert}^2\\ \implies {\left\lVert {x - \sum_{n=1}^\infty {\left\langle {x},~{u_{n}} \right\rangle} u_{n}} \right\rVert}^2 &= {\left\lVert {x} \right\rVert}^2 - \sum_{n=1}^\infty {\left\lvert {{\left\langle {x},~{u_{n}} \right\rangle}} \right\rvert}^2 .\end{align*}
-
Then noting that 0 \leq {\left\lVert {x - S_{N}} \right\rVert}^2, \begin{align*} 0 &\leq {\left\lVert {x} \right\rVert}^2 - \sum_{n=1}^\infty {\left\lvert {{\left\langle {x},~{u_{n}} \right\rangle}} \right\rvert}^2 \\ \implies \sum_{n=1}^\infty {\left\lvert {{\left\langle {x},~{u_{n}} \right\rangle}} \right\rvert}^2 &\leq {\left\lVert {x} \right\rVert}^2 \hfill\blacksquare .\end{align*}
Let \left\{{u_n}\right\}_{n\in A} be an orthonormal set in a Hilbert space {\mathcal{H}}. TFAE:
-
Completeness: \left\{{u_n}\right\} is a complete basis, i.e. {\left\langle {x},~{u_n} \right\rangle}=0 for all n implies x=0
-
Parseval’s identity: \begin{align*} \sum_{n\in A} {\left\lvert { {\left\langle {x},~{u_n} \right\rangle} } \right\rvert}^2 = {\left\lVert {x} \right\rVert}^2_{{\mathcal{H}}} .\end{align*}
-
Every x\in {\mathcal{H}} can be expressed uniquely as \begin{align*} x = \sum_{n\in A} {\left\langle {x},~{u_n} \right\rangle}u_n ,\end{align*} where the sum has only countably many nonzero terms.
If \Lambda is a continuous linear functional on a Hilbert space H, then there exists a unique y \in H such that \begin{align*} \forall x\in H,\quad \Lambda(x) = {\left\langle {x},~{y} \right\rangle} .\end{align*}
proof (?):
- Define M \coloneqq\ker \Lambda.
- Then M is a closed subspace and so H = M \oplus M^\perp
- There is some z\in M^\perp such that {\left\lVert {z} \right\rVert} = 1.
- Set u \coloneqq\Lambda(x) z - \Lambda(z) x
- Check
\begin{align*}\Lambda(u) = \Lambda(\Lambda(x) z - \Lambda(z) x) = \Lambda(x) \Lambda(z) - \Lambda(z) \Lambda(x) = 0 \implies u\in M\end{align*}
- Compute
\begin{align*} 0 &= {\left\langle {u},~{z} \right\rangle} \\ &= {\left\langle {\Lambda(x) z - \Lambda(z) x},~{z} \right\rangle} \\ &= {\left\langle {\Lambda(x) z},~{z} \right\rangle} - {\left\langle {\Lambda(z) x},~{z} \right\rangle} \\ &= \Lambda(x) {\left\langle {z},~{z} \right\rangle} - \Lambda(z) {\left\langle {x},~{z} \right\rangle} \\ &= \Lambda(x) {\left\lVert {z} \right\rVert}^2 - \Lambda(z) {\left\langle {x},~{z} \right\rangle} \\ &= \Lambda(x) - \Lambda(z) {\left\langle {x},~{z} \right\rangle} \\ &= \Lambda(x) - {\left\langle {x},~{\overline{\Lambda(z)} z} \right\rangle} ,\end{align*}
- Choose y \coloneqq\overline{\Lambda(z)} z.
- Check uniqueness:
\begin{align*} {\left\langle {x},~{y} \right\rangle} &= {\left\langle {x},~{y'} \right\rangle} \quad\forall x \\ \implies {\left\langle {x},~{y-y'} \right\rangle} &= 0 \quad\forall x \\ \implies {\left\langle {y-y'},~{y-y'} \right\rangle} &= 0 \\ \implies {\left\lVert {y-y'} \right\rVert} &= 0 \\ \implies y-y' &= \mathbf{0} \implies y = y' .\end{align*}
Let U = \left\{{u_{n}}\right\}_{n=1}^\infty be an orthonormal set (not necessarily a basis), then
- There is an isometric surjection
\begin{align*} \mathcal{H} &\to \ell^2({\mathbb{N}}) \\ \mathbf{x} &\mapsto \left\{{{\left\langle {\mathbf{x}},~{\mathbf{u}_{n}} \right\rangle}}\right\}_{n=1}^\infty \end{align*}
i.e. if \left\{{a_{n}}\right\} \in \ell^2({\mathbb{N}}), so \sum {\left\lvert {a_{n}} \right\rvert}^2 < \infty, then there exists a \mathbf{x} \in \mathcal{H} such that \begin{align*} a_{n} = {\left\langle {\mathbf{x}},~{\mathbf{u}_{n}} \right\rangle} \quad \forall n. \end{align*}
- \mathbf{x} can be chosen such that \begin{align*} {\left\lVert {\mathbf{x}} \right\rVert}^2 = \sum {\left\lvert {a_{n}} \right\rvert}^2 \end{align*}
Note: the choice of \mathbf{x} is unique \iff \left\{{u_{n}}\right\} is complete, i.e. {\left\langle {\mathbf{x}},~{\mathbf{u}_{n}} \right\rangle} = 0 for all n implies \mathbf{x} = \mathbf{0}.
proof (?):
- Given \left\{{a_{n}}\right\}, define S_{N} = \sum^N a_{n} \mathbf{u}_{n}.
- S_{N} is Cauchy in \mathcal{H} and so S_{N} \to \mathbf{x} for some \mathbf{x} \in \mathcal{H}.
- {\left\langle {x},~{u_{n}} \right\rangle} = {\left\langle {x - S_{N}},~{u_{n}} \right\rangle} + {\left\langle {S_{N}},~{u_{n}} \right\rangle} \to a_{n}
- By construction, {\left\lVert {x-S_{N}} \right\rVert}^2 = {\left\lVert {x} \right\rVert}^2 - \sum^N {\left\lvert {a_{n}} \right\rvert}^2 \to 0, so {\left\lVert {x} \right\rVert}^2 = \sum^\infty {\left\lvert {a_{n}} \right\rvert}^2.
Operator Norms
Let L:X \to {\mathbf{C}} be a linear functional, then the following are equivalent:
- L is continuous
- L is continuous at zero
- L is bounded, i.e. \exists c\geq 0 such that {\left\lvert {L(x)} \right\rvert} \leq c {\left\lVert {x} \right\rVert} for all x\in H
proof (?):
2 \implies 3: Choose \delta < 1 such that \begin{align*} {\left\lVert {x} \right\rVert} \leq \delta \implies {\left\lvert {L(x)} \right\rvert} < 1. \end{align*} Then \begin{align*} {\left\lvert {L(x)} \right\rvert} &= {\left\lvert {L\left( \frac{{\left\lVert {x} \right\rVert}}{\delta} \frac{\delta }{{\left\lVert {x} \right\rVert}} x \right)} \right\rvert} \\ &= \frac{{\left\lVert {x} \right\rVert}}{\delta} ~{\left\lvert {L\left( \delta \frac{x }{{\left\lVert {x} \right\rVert}} \right)} \right\rvert} \\ &\leq \frac{{\left\lVert {x} \right\rVert}}{\delta} 1 ,\end{align*} so we can take c = \frac 1 \delta. \hfill\blacksquare
3 \implies 1:
We have {\left\lvert {L(x-y)} \right\rvert} \leq c{\left\lVert {x-y} \right\rVert}, so given \varepsilon \geq 0 simply choose \delta = \frac \varepsilon c.
If H is a Hilbert space, then (H {}^{ \vee }, {\left\lVert {{-}} \right\rVert}_{\text{op}}) is a normed space.
proof (?):
The only nontrivial property is the triangle inequality, but \begin{align*} {\left\lVert {L_{1} + L_{2}} \right\rVert}_{^{\operatorname{op}}} = \sup {\left\lvert {L_{1}(x) + L_{2}(x)} \right\rvert} \leq \sup {\left\lvert {L_{1}(x)} \right\rvert} + {\left\lvert {\sup L_{2}(x)} \right\rvert} = {\left\lVert {L_{1}} \right\rVert}_{^{\operatorname{op}}}+ {\left\lVert {L_{2}} \right\rVert}_{^{\operatorname{op}}} .\end{align*}
If X is a normed vector space, then (X {}^{ \vee }, {\left\lVert {{-}} \right\rVert}_{\text{op}}) is a Banach space.
proof (?):
-
Let \left\{{L_{n}}\right\} be Cauchy in X {}^{ \vee }.
-
Then for all x\in C, \left\{{L_{n}(x)}\right\} \subset {\mathbf{C}} is Cauchy and converges to something denoted L(x).
-
Need to show L is continuous and {\left\lVert {L_{n} - L} \right\rVert} \to 0.
-
Since \left\{{L_{n}}\right\} is Cauchy in X {}^{ \vee }, choose N large enough so that \begin{align*} n, m \geq N \implies {\left\lVert {L_{n} - L_{m}} \right\rVert} < \varepsilon \implies {\left\lvert {L_{m}(x) - L_{n}(x)} \right\rvert} < \varepsilon \quad \forall x {~\mathrel{\Big\vert}~}{\left\lVert {x} \right\rVert} = 1 .\end{align*}
-
Take n\to \infty to obtain \begin{align*}m \geq N &\implies {\left\lvert {L_{m}(x) - L(x)} \right\rvert} < \varepsilon \quad \forall x {~\mathrel{\Big\vert}~}{\left\lVert {x} \right\rVert} = 1\\ &\implies {\left\lVert {L_{m} - L} \right\rVert} < \varepsilon \to 0 .\end{align*}
-
Continuity: \begin{align*} {\left\lvert {L(x)} \right\rvert} &= {\left\lvert {L(x) - L_{n}(x) + L_{n}(x)} \right\rvert} \\ &\leq {\left\lvert {L(x) - L_{n}(x)} \right\rvert} + {\left\lvert {L_{n}(x)} \right\rvert} \\ &\leq \varepsilon {\left\lVert {x} \right\rVert} + c{\left\lVert {x} \right\rVert} \\ &= (\varepsilon + c){\left\lVert {x} \right\rVert} \hfill\blacksquare .\end{align*}